درجة تمثل مبادئ حماية الطفل في حالات الطوارئ لمرحلة رياض الأطفال الواقعة في المناطق المعزولة بمحافظات غزة: دراسة تطبيقية - أبو حشيش، بسام محمد (الجامعة الأردنية - عمادة البحث العلمي, 2019)
The present study aimed to determine the degree to which the principles of child protection in emergency situations of kindergarten in the isolated areas of the Gaza governorates are considered from the viewpoint of both managers, educators and mothers of children. The sample of the study was made up of 151 respondents, including (10) managers, (66) educators and (85) mothers. To answer the questions of the study, a questionnaire was developed as a key tool for collecting information, and after verifying its validity and determination, the questionnaire consisted of (40) paragraphs divided into (6) principles. The study used the descriptive method. The main findings of the study were that the degree of child protection principles in emergency cases of kindergarten reached (2.83) with a percentage of (%56.55) which is an average grade. The results also indicated that there were significant differences between the study sample's responses from managers, educators and the sample of mothers of children, for the benefit of managers and educators.
هدفت الدراسة الحالية إلى تحديد درجة تمثل مبادئ حماية الطفل في حالات الطوارئ لمرحلة رياض الأطفال الواقعة في المناطق المعزولة بمحافظات غزة من وجهة نظر كل من المديرات والمربيات وأمهات الأطفال. حيث تكونت عينة الدراسة من (151) مبحوثة، منها (10) مديرات، و(66) مربية، و(85) أما. وللإجابة عن أسئلة الدراسة تم تطوير استبانة أداة رئيسة لجمع المعلومات، وبعد التحقق من صدقها وثباتها تكونت الاستبانة من (40) فقرة موزعة على (6) مبادئ. وقد استخدمت الدراسة المنهج الوصفي. وقد كانت أبرز نتائج الدراسة بأن درجة تمثل مبادئ حماية الطفل في حالات الطوارئ لمرحلة رياض الأطفال قد بلغ (2.83) بنسبة (56.55%) وهي درجة متوسطة. كما أشارت النتائج بوجود فروق معنوية بين استجابات عينة الدراسة من المديرات والمربيات وعينة أمهات الأطفال، وذلك لصالح المديرات والمربيات.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- طرق التدريس -- التعليم قبل المدرسي -- رياض الأطفال -- قانون حماية الطفل -- قطاع غزة -- فلسطين -- المجتمع الفلسطيني -- مستخلصات الأبحاث